Neuroprotective Efficacy of Clitoria Ternacea Root Extract on Hippocampal CA3 Neurons – A Quantitative Study in Mice - Hemamalini, Shetty; Rao, Muddanna S. (Journal of Morphological Sciences, 2018)
Clitoria ternatea is a vigorous, herbaceous perennial legume that belongs to the Fabaceae family. All parts of the plant are used in the preparations of Ayurvedic drugs. It is an astringent, an aphrodisiac, a rejuvenator, and a brain tonic. It also has anti-inflammatory, analgesic, and antipyretic properties. Baidyanath Shankapushpi, which contains extracts of herbs such as C. ternatea, Bacopa monnieri, Withania somnifera and Asparagus racemosus, is clinically administered for memory improvement, blood purification and to improve digestion. However, its neuroprotective effect has not been reported so far. In the present study, the neuroprotective effect of C. ternatea root (CTR) extract on hippocampal CA3 neurons was investigated. Three-month-old albino mice were divided into four groups. Group I was the normal control, group II was the saline control, group III was the stress group, and group IV was the stress + CTR-treated group. Group-III mice were stressed in a wire mesh restrainer for 6 hours/day for 6 weeks. Grou-IV mice were also stressed like group III, but received CTR extract orally throughout the stress period. After 6 weeks, their brain was removed, and their hippocampi were dissected and processed for Golgi staining. The hippocampal neurons were traced using a camera lucida focused at 400x magnification. The Sholl concentric circle method was used to quantify the dendrites. The results showed a decrease in the number of dendritic branching points and of dendritic intersections in the stressed group. On the other hand, there was an increase in the number of dendritic branching points and of dendritic intersections of hippocampal CA3 neurons in group IV, which was subjected to restraint stress and was treated with the CTR extract. The results showed that the oral administration of CTR significantly increased the dendritic branching points and the dendritic intersections of hippocampal CA3 neurons.
Keywords: restraint stress; dendritic branching points; dendritic intersections; hippocampus